THE ESSENCE, STRUCTURE, AND DEVELOPMENTAL CHARACTERISTICS OF ARTISTIC TASTE AND AESTHETIC THINKING IN STUDENTS (SCIENCE TIME JOURNAL, 2026)
This article provides a comprehensive scientific and theoretical analysis of the problem of developing artistic taste and aesthetic thinking among students in higher education, closely connected with the process of visual art perception. The study reveals the psychological, didactic, and semiotic mechanisms of art perception based on the integration of aesthetic, cognitive, moral, cultural, andpedagogical factors. The processes of visual perception, compositional thinking, color sensitivity, artistic analysis, retation, and emotional-intellectual responses are examined within a systemic methodological framework. The results of the study are of both theoretical and practical significance for improving contemporary methodologies in art education.